Metagenomic insights reveal the differences in the community composition and functional characteristics of the sea turtle microbiomes based on host species and tissue region - Dong, Lingzhi; Du, Yu; Qiu, Feifei; Zhang, Meng; Wang, Xiaoxia; Zhu, Xiaming; Yao, Yuntao; Li, Jinyi; Ji, Xiang; Zhu, Xiong (Frontiers in Microbiology, 2025)
Introduction and methodsSea turtles have been proposed as health indicators of marine ecosystems for their characteristic of longevity and migratory, but they are facing serious threats due to various factors. The microbial communities within animals play an important role in health and disease. Our study aims to explore a thorough evaluation of the sea turtle microbiome by examining the oral, nasal, and cloacal microbial communities of three species: green turtles, hawksbills, and loggerheads, through metagenomic sequencing.ResultsUtilizing approximately 705.81 GB of metagenomic sequencing data from 63 samples collected from different turtle species and tissue regions, we created a nonredundant sea turtle microbial gene catalog (STMGC) containing 10,733,232 unique genes through the de-redundancy of open reading frames (ORFs). Our findings revealed that the sea turtle microbiomes were primarily composed of Pseudomonadota (formerly Proteobacteria) and Bacteroidota (formerly Bacteroidetes). The tissue region was a key factor affecting the variability in the sea turtle microbiome, with green turtles showing notable differences among the three turtle species. Pseudomonadota was significantly more abundant in oral samples, while Bacteroidota was more prevalent in nasal samples. Campylobacterota was identified as significantly more abundant in cloacal samples. Importantly, we discovered 389 genera and 1,445 species of potential pathogens within the sea turtle microbiome, indicating potential pathogenic risks that warrant further investigation alongside culturomics. Additionally, our study highlighted significant functional differences among the three turtles and tissue regions. It is worth noting that among the three sea turtles, antibiotic resistance genes are more prevalent in hawksbills, while virulence genes are more abundant in loggerheads. Moreover, within the three tissue regions, antibiotic resistance genes are higher in oral samples, while virulence genes are more extensive in cloacal samples.ConclusionThe findings in our study demonstrate that the microbial composition and function in these sea turtles exhibit both species-specific and region-specific variations. The implications of these associations and the underlying mechanisms not only provide valuable insights for future studies on the microbial communities of turtles, but also lay the foundation for further research on the health interrelationships among sea turtles, marine and terrestrial animals, humans and the environment, and for defining “One Health” factors.